Double site saturation mutagenesis of the human cytochrome P450 2D6 results in regioselective steroid hydroxylation. (3rd May 2013) - Geier, Martina; Braun, Andreas; Fladischer, Patrik; Stepniak, Piotr; Rudroff, Florian; Hametner, Christian; Mihovilovic, Marko D.; Glieder, Anton
<x xml:space="preserve">Abstract</x> The human cytochrome P450 2D6 (CYP2D6) is one of the major human drug metabolizing enzymes and acts preferably on substrates containing a basic nitrogen atom. Testosterone − just as other steroids − is an atypical substrate and only poorly metabolized by CYP2D6. The present study intended to investigate the influence of the two active site residues 216 and 483 on the capability of CYP2D6 to hydroxylate steroids such as for example testosterone. All 400 possible combinatorial mutations at these two positions have been generated and expressed individually in Pichia pastoris. Employing whole‐cell biotransformations coupled with HPLC‐MS analysis the testosterone hydroxylase activity and regioselectivity of every single CYP2D6 variant was determined. Covering the whole sequence space, CYP2D6 variants with improved activity and so far unknown regio‐preference in testosterone hydroxylation were identified. Most intriguingly and in contrast to previous literature reports about mutein F483I, the mutation F483G led to preferred hydroxylation at the 2β‐position, while the slow formation of 6β‐hydroxytestosterone, the main product of wild‐type CYP2D6, was further reduced. Two point mutations have already been sufficient to convert CYP2D6 into a steroid hydroxylase with the highest ever reported testosterone hydroxylation rate for this enzyme, which is of the same order of magnitude as for the conversion of the standard substrate bufuralol by wild‐type CYP2D6. Furthermore, this study is also an example for efficient human CYP engineering in P. pastoris for biocatalytic applications and to study so far unknown pharmacokinetic effects of individual and combined mutations in these key enzymes of the human drug metabolism.